Drying behaviour of green beans - Doymaz, I (ELSEVIER SCI LTD, 2005)
This paper presents the thin layer drying experiments and mathematical modelling of green bean grown in Iskenderun, Turkey. Drying characteristics of green bean were examined for average moisture content from 90.53 +/- 0.5% to 14 +/- 0.3% using hot air of the temperature range of 50-70 degrees C. The results have shown that, increasing the drying air temperature causes shorter drying times. The experimental drying curves obtained were fitted to a number of semi-theoretical models, namely Handerson and Pabis, Lewis and Page models. Comparing the determination of coefficient, reduced chi-square and root mean square error values of three models, it was concluded that the Page model represents drying characteristics better than the others. The effective diffusivity coefficient of moisture transfer varied from 2.641 x 10(-9) to 5.711 X 10(-9)m(2)/s over the temperature range. The temperature dependence of the diffusivity coefficients was described by Arrhenius type relationship. The activation energy for moisture diffusion was found to be 35.43 kJ/mol. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: drying of green bean; drying rate; modelling; moisture diffusivity; THIN-LAYER; RED-PEPPER; KINETICS; SOYBEANS; Engineering; Food Science & Technology